Developing Listening Skills For The Toeic Test : Persiapan Tes Toeic Untuk Karir Yang Lebih Baik - Slamet Riyanto (Pustaka Pelajar, 2008)
Question and Answer seputar Tes Toeic, Developing Listening Skill, dan Practice Test for Toeic Tests.